Die Islandfahrt des Columbus vom Jahre 1477 - Graefe, Hanns (ERDKUNDE, 1955)
This paper attempts to prove that the report of Columbus’s voyage to Iceland, the verity of which has been widely disputed, is nevertheless genuine. The negative criticism is largely based on the following statements made in the report: 1. a tidal range of 25 fathoms, which for Iceland is quite impossible; 2. the latitude, which is in correct; 3. the most peculiar fact that a voyage into arctic waters should have been carried out in mid-winter. Against these three points the following counter arguments are put forward: 1. the calculation of the tidal range should not be based on the length of the present day Spanish fathom (braza) of 1.6718 m. but on the Arabic ell (covid) of 0.4886 m. since Spain at the time of Columbus was still partly under Arabic domination and to an even greater degree under Arabic cultural influence; 2. the alleged wrong latitude by no means refers to Iceland. Columbus distinguished two islands, one of which is supposed to be situated 100 leguas beyond Iceland at 73° N.; this might perhaps refer to the island of Jan Mayen; 3. the fact, mentioned in Columbus's report that the sea was free of ice is corroborated by the evidence of Finn Magnussen who found by means of old records that in February 1477 the south coast of Iceland was indeed ice free. It is quite impossible that this fact could have been known to an in habitant of the Iberian peninsula except as a result of personal experience. This, it is suggested, should serve as the main argument in support of the authoritative character of Columbus's report.